Nanometer Technology Designs High-Quality Delay Tests - Tehranipoor, Mohammad; Ahmed, Nisar; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
While adopting newer, better fabrication technologies provides higher integration and enhances performance, it also increases the types of manufacturing defects. With design size in millions of gates and working frequency in GHz, timing-related defects have become a high proportion of the total chip defects. For nanometer technology designs, the traditional test methods cannot ensure a high quality level of chips, and at-speed tests using path and transition delay fault model have become a requirement in technologies below 180nm. Nanometer Technology Designs: High-Quality Delay Tests discusses these challenges in detail and proposes new techniques and methodologies to improve the overall quality of the delay test for nanotechnology designs. Topics covered include: At-speed test challenges for nanotechnology Low-cost tester-friendly design-for-test techniques Improving test quality of current at-speed test methods Functionally un-testable fault list generation and avoidance Timing-based ATPG for screening small delay faults Faster-than-at-speed test considering power supply noise Power supply noise tolerant at-speed test pattern generation and application Solutions for dealing with crosstalk and signal integrity issues Nanometer Technology Designs: High-Quality Delay Tests is a reference for practicing engineers and researchers in both industry and academia who are interested in learning about and implementing the most-advanced methods in nanometer delay testing.
Introduction to path delay and transition delay fault models and test methods -- At-speed test challenges for nanometer technology designs -- Low-cost tester friendly design-for-test techniques -- Improving test quality of current at-speed test methods -- Functionally untestable fault list generation and avoidance -- Timing-based ATPG for screening small delay faults -- Faster-than-at-speed test considering IR-drop effects -- IR-drop tolerant at-speed test pattern generation and application.
Keywords: Engineering; Computer-aided engineering; Electrical engineering; Electronics; Microelectronics; Electronic circuits; Nanotechnology; Engineering; Circuits and Systems; Electronics and Microelectronics, Instrumentation; Computer-Aided Engineering (CAD, CAE) and Design; Nanotechnology; Electrical Engineering; Electronic books